Board leadership structure and earnings quality - Chinedu Francis Egbunike; Augustine N. Odum (Asian Journal of Accounting Research, 2018)
One main concern and issue affecting earnings quality is the extent to which managers manipulate earnings to mislead stakeholders about the underlying economic performance of the company or to influence contractual outcomes that depend on reported accounting numbers. This study builds on prior research and examines empirically the relationship between board leadership structure and earnings quality of manufacturing firms in Nigeria. The purpose of this paper is to specifically focus on four board structure characteristics: board size, composition, proportion of non-executive directors and CEO duality.Data used for this investigation were collected from secondary sources, i.e. annual reports and accounts. The study used the Pooled OLS regression model to examine the effect of the board structure on earnings management for a sample of 45 non-financial listed Nigerian companies (conglomerates, consumer goods and industrial goods firms) for the years 2011 to 2016.Based on the analysis, board size and board composition were positive and significant. However, proportion of non-executive directors was negative and significant; while, CEO duality was positive and statistically significant. It was consequently recommended that audit firms should review their audit business model and become more circumspect of their client, e.g. provide fraud assessment and checks for earnings quality. Boards should not just reflect size but rather the skills and expertise of individuals appointed to the board. Furtherance to this, the effectiveness of boards can be improved by committees and sub-committees allocation of duties.Few studies have addressed this area in the country.